Cryptomimesis : the gothic and Jacques Derrida's ghost writing - Castricano, Carla Jodey, 1947- (McGill-Queen's University Press, 2001)
She develops the theory of cryptomimesis, a term devised to accommodate the convergence of philosophy, psychoanalysis, and certain "Gothic" stylistic, formal, and thematic patterns and motifs in Derrida's work that give rise to questions regarding writing, reading, and interpretation. Using Edgar Allan Poe's Madeline and Roderick Usher, Bram Stoker's Dracula, and Stephen King's Louis Creed, she illuminates Derrida's concerns with inheritance, revenance, and haunting and reflects on deconstruction as ghost writing. Castricano demonstrates that Derrida's Specters of Marx owes much to the Gothic insistence on the power of haunting and explores how deconstruction can be thought of as the ghost or deferred promise of Marxism. She traces the movement of the "phantom" throughout Derrida's other texts, arguing that such writing provides us with an uneasy model of subjectivity because it suggests that "to be" is to be haunted. Castricano claims that cryptomimesis is the model, method, and theory behind Derrida's insistence that to learn to live we must learn how to talk Awith" ghosts.